Insulin receptor substrate‐1 (IRS‐1) forms a ribonucleoprotein complex associated with polysomes. Issue 15 (13th June 2013) - Ozoe, Atsufumi; Sone, Meri; Fukushima, Toshiaki; Kataoka, Naoyuki; Arai, Toshiya; Chida, Kazuhiro; Asano, Tomoichiro; Hakuno, Fumihiko; Takahashi, Shin-Ichiro
Abstract : Insulin receptor substrates (IRSs) are known to play important roles in mediating intracellular insulin‐like growth factors (IGFs)/insulin signaling. In this study, we identified components of messenger ribonucleoprotein (mRNP) as IRS‐1‐associated proteins. IRS‐1 complex formation analysis revealed that IRS‐1 is incorporated into the complexes of molecular mass more than 1000 kDa, which were disrupted by treatment with RNase. Furthermore, oligo(dT) beads precipitated IRS‐1 from cell lysates, showing that the IRS‐1 complexes contained messenger RNA. Taken together with the data that IRS‐1 was fractionated into the polysome‐containing high‐density fractions, we concluded that IRS‐1 forms the novel complexes with mRNPs. Abstract : IRS‐1 forms complexes with messenger RNA. IRS‐1 interacts with PABPC1, eIF4E and eIF4G in RNA‐dependent manner. IRS‐1 is distributed into high‐density fractions containing polysomes in proliferating cells.